Troponins in experimental studies - Adamcová, Michaela; Gersl, Vladimír; Machácková, Jarmila; Hrdina, Radomír; Klimtová, Ivona; Simůnek, Tomás; Vávrová, Jaroslava; Bukac, Josef (Acta medica (Hradec Kralove), 2002)
The aim of our study was to compare the diagnostic performance of cardiac troponin T (cTnT) and cardiac troponin I (cTnI) in three groups of rabbits: 1) control (saline 1 ml/kg i.v.); 2) daunorubicin (3 mg/kg i.v.); 3) daunorubicin (3 mg/kg i.v.) + dexrazoxane (60 mg/kg i.p.). The drugs were given once a week, 10 administrations. The concentration of cTnT was measured using Elecsys Troponin T STAT Immunoassay (Roche). The concentration of cTnI was measured using AxSYM Troponin I (Abbott). The linear regression model was applied to see if there is a dependence between cTnT and cTnI. The coefficient of determination (R2 = 0.79) was acceptable only in the control group. In the remaining cases (i.e. in the daunorubicin group and in the daunorubicin + dexrazoxane treated group) R2 was too small (0.53, and 0.06). We may conclude that in rabbits after repeated administration of cardiotoxic or cardioprotective drugs meaningful dependence between cTnT and cTnI was not found. The choice of the most suitable cardiomarker in laboratory animals deserves further studies.
Keywords: Troponin T; Animals; biologické markery; Antibiotics, Antineoplastic; Protective Agents; ochranné látky; Razoxane; mužské pohlaví; kardiomyopatie; Daunorubicin; Heart; zvířata; srdce; troponin T; Cardiomyopathies; razoxan; králíci; Biomarkers; Male; protinádorová antibiotika; daunomycin; Rabbits